Case Report: Challenging Treatment of an AorticParavalvular Leak: How We Avoided Interference With Mechanical Valve Function? - Onorato, Eustaquio Maria; Vercellino, Matteo; Costante, Annamaria; Bartorelli, Antonio L. (Frontiers in Cardiovascular Medicine, 2022)
Background Aortic paravalvular leak (APVL) after surgical valve replacement (AVR) is an ominous complication with a high risk of morbidity and mortality. Approximately 1–5% of PVLs can lead to serious clinical consequences, including congestive heart failure and/or hemolytic anemia. Case Summary A 69-year-old man with multiple comorbidities underwent surgical replacement of the aortic valve with a mechanical tilting disc prosthetic valve (Medtronic Starlight 27 mm). Several years later, recurrent episodes of congestive heart failure and hemolytic anemia developed due to a large crescent-shaped aortic PVL located at non coronary cusp (NCC) 9–12 o'clock, with moderate-to-severe regurgitation. The patient was deemed at prohibitive surgical risk due to significant multiple comorbidities and a transcatheter PVL closure (TPVLc) was planned. The huge PVL was partially closed by a first specifically designed paravalvular leak device (PLD). The procedure was complicated by transient interference of the second PLD with mechanical prosthetic valve function. This issue has however been solved with correct manipulation, orientation and downsizing of the second device implanted. At 3-month and 13-month follow-up, the patient showed a relevant clinical improvement and good quality of life. 2D TTE color Doppler confirmed the stable position of the two PLDs with trace residual leak. Discussion Surgical redo has been considered the treatment of choice for symptomatic patients with PVLs. Notwithstanding, TPVLc is a less invasive alternative, particularly in patients at high surgical risk in whom early diagnosis and prompt interventional treatment are crucial for improving expectancy and quality of life. Dedicated devices, appropriate procedural techniques, and the close interaction between imaging modalities, allowed to deal successfully with a challenging case of severe symptomatic aortic PVL.